On numerical study of calcium sulphate fouling under sub-cooled flow boiling conditions - Haghshenasfard, M.; Yeoh, G.H.; Dahari, M.; Hooman, K. (Elsevier, 2015)
Fouling rate of calcium sulphate is investigated based on the development of a multicomponent model to handle the two-phase flow of liquid mixture and vapour bubbles for the sub-cooled flow boiling. Effects of operating conditions, as well as wall roughness, on the heat transfer and fouling rate are studied. Fouling resistance increased with increasing fluid velocity. Deposition rate increases rapidly with increasing surface temperature while heat transfer coefficient decreases at higher surface temperature. Nevertheless, the bulk temperature does not strongly influence the heat transfer coefficient, thermal resistance and fouling rate. (C) 2015 Elsevier Ltd. All rights reserved.